2020 14th European Conference on Antennas and Propagation (EuCAP) 2020
DOI: 10.23919/eucap48036.2020.9135281
|View full text |Cite
|
Sign up to set email alerts
|

Image Improvement Through Metamaterial Technology for Brain Stroke Detection

Abstract: In this paper we investigate the capabilities of metamaterials technology to enhance the quality of reconstructed images for the problem of brain stroke detection. We integrate the metamaterial in our headband system for brain imaging in CST, and evaluate the reconstructed images of the head model that is placed inside the microwave tomographic head system for the cases with and without the incorporated metamaterial. For image reconstruction we apply the distorted Born iterative method (DBIM) combined with two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 17 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…In our previous study [ 19 ], we have already shown the benefits of using MTS-enhanced antennas. In this section, we present experimental results for both the arrays described in Section 2.2 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In our previous study [ 19 ], we have already shown the benefits of using MTS-enhanced antennas. In this section, we present experimental results for both the arrays described in Section 2.2 .…”
Section: Resultsmentioning
confidence: 99%
“…To test the performance of our new PSMA and MTS-enhanced PSMA operating in air, we compared our previous developed brain scanner operating in an infinite lossy matching medium to two tomographic systems: an 8-PSMA system and an 8-MTS-enhanced PSMA system. Our previous developed MWT scanner for brain imaging consists of 12 spear patch antennas immersed in a 90% glycerol-water mixture and placed around EN 50361 Specific Anthropomorphic Mannequin (SAM) head model [ 18 , 19 ]. A similar setup (“System 1”), including 8 antennas placed elliptically around our numerical head model, was modelled in CST Microwave Studio.…”
Section: Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Valeria Mariano's team at the Polytechnic University of Turin used a dataset generated by full-wave simulation to test the type and direction of stroke [15]. The group of King's College London, Strand, London, applied the distorted Born iterative method, two-step iterative shrinkage thresholding (DBIM-TwIST) algorithm to differentiate the hemorrhagic and S ischemic strokes [16], [17], [18]. In the latest study, the team from Czech Technical University used support vector machines (SVMs) to establish a comprehensive training set, which can classify hemorrhagic stroke and ischemic stroke [19].…”
Section: ) (Corresponding Author: Ming Yu)mentioning
confidence: 99%
“…[16], [17], [18] Discriminate between ischemic and hemorrhagic stroke and imaged. The effect of the presence or absence of metamaterials on the effectiveness was compared.…”
Section: Differential Approximations and Distortedmentioning
confidence: 99%